The Value of Serum Adiponectin in Osteoporotic Women: Does Weight Have an Effect? - Ali B. Roomi; Wassan Nori; Saad H. Al-Badry (Hindawi Limited, 2021)
Osteoporosis (OP) has been observed to have a deleterious effect on postmenopausal women's life quality by increasing the risk of fragility fractures. The current research was adopted to verify the role of serum adiponectin, a cytokine released by adipose tissue, as a marker for OP across different body mass index groups, for a better understanding of fatty tissue role in OP. A case-control study recruited 210 eligible postmenopausal women and subgrouped into three groups based on their DEXA scan results: osteoporotic group, osteopenia group, and healthy controls; each includes 70 patients. Three datasets were collected: anthropometric, age, menopause duration, weight, height, body mass index (BMI), waist circumference, and fat percentage. Radiological examination estimated the bone mineral density (BMD) for the femoral neck and lumbar spines with their respective T-score. From blood, we measured alkaline phosphatase and calcium by a spectrophotometer and serum adiponectin, phosphate, CTX, and PICP by ELIZA. Total BMD, T-score, serum phosphate, and PICP were significantly higher among healthy controls. Serum adiponectin, CTX, and ALP scored higher levels among OP cases. A strong inverse relationship was proved between serum adiponectin and T-score in osteoporotic and osteopenia groups (−0.427, −0.301). A strong negative relationship was found between serum adiponectin and total BMD in healthy controls (−0.204). All correlations were statistically significant, P value <0.001. Serum adiponectin can be a valuable marker for reduced bone mineral density among the general populace, irrespective of the body mass index. Further research is warranted to explore therapeutic and preventive applications for this adipocytokine.